Patrimonializar al indígena. Imaginación del multiculturalismo neoliberal en Chile - Guillaume Boccara; Patricia Ayala (Cahiers des Amériques Latines)
Since the end of the dictatorship, there has been a redefinition of the relationships between the Chilean State and the indigenous peoples. A new political, legal and ideological framework has been implemented in order to deal with the so-called “indigenous problem” and multiculturalism has become the new buzzword of official discourses. In this essay, we shall focus on the political nature of this new national and nationalizing project called multiculturalism through the examination of the patrimonializing process of the indigenous cultures and past. Drawing on the critical anthropology of development and of the neoliberal State, we shall concentrate on the Council of National Monuments’ new policy that contributes to the reimagining of the nation through the transformation of indigenous cultures into national patrimony and economic resource. We shall then draw some general conclusions regarding the nature of neoliberal multiculturalism and the shaping of what we call ethnogovernmentality.